A Canadian approach to the regionalization of testis cancer: A review - Nason, Gregory J.; Wood, Lori A.; Huddart, Robert A.; Albers, Peter; Rendon, Ricardo A.; Einhorn, Lawrence H.; Nichols, Craig R.; Kollmannsberger, Christian; Anson-Cartwright, Lynn; Sweet, Joan; Warde, Padraig; Jewett, Michael A.S.; et al. (Canadian Urological Association Journal, 2020)
At the Canadian Testis Cancer Workshop, the rationale and feasibility of regionalization of testis cancer care were discussed. The two-day workshop involved urologists, medical and radiation oncologists, pathologists, radiologists, physician’s assistants, residents and fellows, and nurses, as well as patients and patient advocacy groups. This review summarizes the discussion and recommendations of one of the central topics of the workshop — the centralization of testis cancer in Canada. It was acknowledged that non-guideline-concordant care in testis cancer occurs frequently, in the range of 18–30%. The National Health Service in the U.K. stipulates various testis cancer care modalities be delivered through supraregional network. All cases are reviewed at a multidisciplinary team meeting and aspects of care can be delivered locally through the network. In Germany, no such network exists, but an insurance-supported online second opinion network was developed that currently achieves expert case review in over 30% of cases. There are clear benefits to regionalization in terms of survival, treatment morbidity, and cost. There was agreement at the workshop that a structured pathway for diagnosis and treatment of testis cancer patients is required. Regionalization may be challenging in Canada because of geography; independent administration of healthcare by each province; physicians fearing loss of autonomy and revenue; patient unwillingness to travel long distances from home; and the inability of the larger centers to handle the ensuing increase in volume. We feel the first step is to identify the key performance indicators and quality metrics to track the quality of care received. After identifying these metrics, implementation of a “networks of excellence” model, similar to that seen in sarcoma care in Ontario, could be effective, coupled with increased use of health technology, such as virtual clinics and telemedicine.